Exocellular peptides from Antarctic Psychrophile Pseudoalteromonas haloplanktis. - Mitova M; De Rosa S.; TUTINO, MARIA LUISA; INFUSINI, GIUSEPPE; MARINO, GENNARO (2005)
A novel diketopiperazine, named cyclo-(D-pipecolinyl-L-isoleucine) (DKP 1), and 7 known diketopiperazines were isolated from the cell-free culture supernatant of the Antarctic psychrophilic bacterium Pseudoalteromonas haloplanktis TAC125. Two diketopiperazines containing pipecolinyl moiety were isolated for the first time from a natural source. Two new linear peptides, stable to bacterial proteolytic enzymes, were also characterized. The structures of the isolated compounds were elucidated by means of spectroscopic data (1D-, 2D-NMR, EIMS, FABMS, and ESIMS/MS) and chiral high-performance liquid chromatography. The potential antioxidant activity of the isolated compounds was evaluated by a DPPH free radical scavenging assay.